Assessing the legitimacy of flood risk governance arrangements in Europe: insights from intra-country evaluations. Issue 8 (17th November 2017) - Pettersson, Maria; van Rijswick, Marleen; Suykens, Cathy; Alexander, Meghan; Ek, Kristina; Priest, Sally
ABSTRACT: Legitimacy has received comparatively less attention than societal resilience in the context of flooding, thus methods for assessing and monitoring the legitimacy of flood risk governance arrangements are noticeably lacking. This study attempts to address this gap by assessing the legitimacy of flood risk governance arrangements in six European countries through cross-disciplinary and comparative research methods. On the basis of this assessment, recommendations to enhance the legitimacy of flood risk governance in Europe are presented.